Demokrasi - Istari Nisa Umita; Feni Windi Astuti; Atik Carolina Dio (Penerbit Yayasan Daarul Huda Kruengmane, 2023)
In managing their government, many countries use a democratic system. One of them is Indonesia. Democracy that is currently used is the influence of the concept of modern democracy. Where the highest sovereignty holders are in the hands of the people and carried out based on the 1945 Constitution. Indonesia has experienced several changes in the democratic system. This journal has a goal so that readers can understand and implement democracy in the life of the nation and state. This study uses a descriptive approach method whose basic discussion is obtained from various sources such as books, journals and articles. With the topic raised, namely democracy, the writer is interested in analyzing this because it is very important to develop knowledge about democracy for the nation and state.